Towards Posthumanist Design: With-Water - Meaney, Lisa (FormAkademisk, 2013)
The article presents an investigation into the performative as developed by Hensel (2010) and the posthumanist as developed by Haraway (1988) within a broadly architectural context. By assuming the agency and continuous becoming of the material world, the culturally located and anthropocentric notion of the designer is called into question. The practice of posthumanist and performative design collaboration across the human-nonhuman spheres is presented as analternative. The development of a collaborative process between water as matter, and the maker/designer is the focus. A practice based investigation of theoretical ideas around agency, irony, relational dialectics and situated andembodied knowledge as developed by Barad (2003), Haraway (1988) and Linton (2010) is documented through a series of collaborative experiments with water.The article concludes that the enactment of our human-nonhuman, material-semiotic relationships precludes our knowledge. It posits the process based practice of designing from a performative and posthumanist site of irony, embodiment and continuous socio-natural becoming as an effective environmental strategy for design.